DEVELOPMENT OF CULTURAL TOURISM TOWARDS THE SUSTAINABLE ECONOMY OF LOCAL COMMUNITIES - Qianrui, Wang (Asia Pacific Journal of Religions and Cultures, 2025)
Cultural tourism there is a variety of details such as sightseeing tours. ruins of the past admire the beauty of ancient objects, the way of life of people in the community Participating in important traditions of that nation, including going to temples to make merit and vipassana meditation including the diversity of ethnic groups that have continued to inherit the local identity of the group. Therefore, it can attract the attention of tourists. Ability to access a variety of tourist attractions, both naturally occurring and man-made. Between cultural tourism and tourism field trip Buddhist tourism. Present, it is found that cultural tourism is about to disappear due to the influence of changes in technology. social change. Therefore, there must be development of cultural tourism management, tourism development that can be conscious of conservation of natural and cultural resources. However, it is necessary to have an important development component, namely having an organization for management. There is a good management system. There is support for the development of quality of life and community economy. Promoting community culture, caring for the environment together in the community creating learning and having good service, rebalancing to promote sustainable cultural tourism Support participation in the promotion of cultural tourism that is socially and environmentally responsible, provided that the development guidelines must truly come from the needs of the community and lead to economic sustainability of the community.